IMPORTANCE OF LINGUISTIC COMPETENCE AND FACTORS INFLUENCING ON THE ISSUE - Khamrayeva Shahlo Shuxratovna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Understanding how linguistic competence evolves in students is not only of theoretical interest but also of practical significance. Proficiency in language is closely tied to academic achievement, as language serves as the medium through which knowledge is acquired, expressed, and assessed. Linguistic competence, the ability to comprehend and produce language accurately, is a fundamental skill in human communication and plays an essential role in academic success. This article discusses issues of linguistic competence development in students and deals with the factors influencing linguistic competence, including environmental, genetic, and educational factors, while highlighting the importance of fostering linguistic competence in educational settings